Cover Image, Volume 139, Issue 1. Issue 1 (22nd September 2021) - Ma, Youmei; Zhang, Shuling
Abstract : In the article from Shuling Zhang and Youmei Ma, Silica nanoparticles with a refractive index matching poly (propylene carbonate) (PPC) and a diameter smaller than the visible light wavelength were chosen to prepare transparent PPC/silica nanocomposites with enhanced properties using a simple melt compounding method. Details can be found in their article. DOI: 10.1002/app.51513